Penerapan Game Based Learning dalam Meningkatkan Kemampuan Literasi dan Numerasi Siswa di SDN 1 Citalang Kecamatan Purwakarta - Lilis Lise Suhartati; Siti Misliah; Suharyanto H. Soro; Ida Tejawiani (Civiliza Publishing, Indonesia., 2026)
This study aims to describe the implementation of Game Based Learning (GBL) in improving students' literacy and numeracy skills at SDN 1 Citalang, Purwakarta District. The researcher used a qualitative research paradigm with a case study approach. Respondents in the study included class teachers and students directly involved in the implementation of GBL. Data collection methods were carried out through observation, semi-structured interviews, and documentation. Data analysis used the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study showed that (1) The implementation of GBL was carried out through three stages: planning which included identifying needs and selecting educational games, implementation which integrated games with literacy and numeracy materials, and process-based and outcome-based evaluation; (2) Students' responses to GBL were very positive, indicated by increased motivation, active involvement, and enthusiasm in participating in learning; (3) Supporting factors for the implementation of GBL included the availability of infrastructure, teacher creativity, and the characteristics of elementary school-aged students who enjoy playing activities; (4) Inhibiting factors were limited time, technological readiness, and difficulty in managing class dynamics. This study concludes that GBL is effective in improving students' literacy and numeracy skills and is recommended as an innovative learning strategy in elementary schools.